2017
DOI: 10.3892/ijo.2017.3987
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of circadian gene 'hClock' contribution to metastasis of colorectal cancer

Abstract: Recent studies have shown that disruption of the circadian rhythm was one of the endogenous factors contributing to tumorigenesis of various human malignancies, including colorectal cancer (CRC). However, the roles of circadian genes in the development of CRC are still unexplored. In this study, we investigated the expression pattern and the underlying mechanism of human Clock gene (hClock) in CRC progression. Multiple methods such as qRT-PCR, immunohistochemistry, and western blotting were performed to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
(38 reference statements)
1
24
0
Order By: Relevance
“…Importantly, mice with mutations in the Bmal1 gene show premature aging phenotype [15]. In addition, human CLOCK has been suggested to be involved in metastasis of colorectal cancer [16]. These findings implicate the core circadian machinery in the regulation of DDR and the cell cycle.…”
Section: Possible Roles Of Clock Proteins In Functional Regulation Ofmentioning
confidence: 97%
“…Importantly, mice with mutations in the Bmal1 gene show premature aging phenotype [15]. In addition, human CLOCK has been suggested to be involved in metastasis of colorectal cancer [16]. These findings implicate the core circadian machinery in the regulation of DDR and the cell cycle.…”
Section: Possible Roles Of Clock Proteins In Functional Regulation Ofmentioning
confidence: 97%
“…CLOCK k/d cells also had reduced metastatic potential in mice and reduced expression of HIF1α, ARNT and VEGF, all known to be key players in angiogenesis (Wang et al, 2017). In vitro, SW620 cells endogenously expressing high levels of CLOCK showed decreased proliferation and decreased cell migration after CLOCK k/d, while CLOCK overexpression in an endogenously low expressing cell line, SW480, resulted in the opposite effect (Wang et al, 2015b, Wang et al, 2017. CLOCK k/d in U87MG cells (human glioblastoma) increased apoptosis, along with decreased MYC and CCNB1 (Cyclin B1) (Wang et al, 2016).…”
Section: Clockmentioning
confidence: 99%
“…Mechanistic interrogation found that overexpressing CLOCK caused a decrease in apoptosis related proteins BAX and BID and an increase in p-AKT (Wang et al, 2015b). CLOCK k/d cells also had reduced metastatic potential in mice and reduced expression of HIF1α, ARNT and VEGF, all known to be key players in angiogenesis (Wang et al, 2017). In vitro, SW620 cells endogenously expressing high levels of CLOCK showed decreased proliferation and decreased cell migration after CLOCK k/d, while CLOCK overexpression in an endogenously low expressing cell line, SW480, resulted in the opposite effect (Wang et al, 2015b, Wang et al, 2017.…”
Section: Clockmentioning
confidence: 99%
“…Female nurses with long-term rotating night shift work had an increased risk for breast cancer (30). In addition, increased expression of the circadian gene hClock may contribute to tumorigenesis, such as the metastasis of colorectal cancer, through the enhanced expression of angiogenesis-related genes (31). …”
Section: Circadian Rhythm In Degenerative Disease and Cancermentioning
confidence: 99%